Justice alternatives - Carlen, Pat; França, Leandro Ayres (Abingdon, Oxon Routledge, 2020)
Justice is one of the most debated and reinterpreted of concepts within the fields of law, criminology and criminal justice. Bringing together 35 leading thinkers, analysts and campaigners from around the world, this collection presents a range of on-going struggles for justice from abolitionist, transitional, transformative, indigenous, green and restorative perspectives.

Against a background of contemporary concerns about dark money, plutocracies and populism, these chapters raise questions about the relationships between social justice and criminal justice and between democracy, knowledge and justice. Overall, the chapters also demonstrate the breadth, variety and vibrancy of contemporary criminology and include, amongst other cutting-edge contributions, chapters by John Braithwaite, Michelle Brown, Ian Loader, Pat O’Malley, Joe Sim, Susanne Karstedt, Phil Scraton, Richard Sparks, Loïc Wacquant and Sandra Walklate.

Justice Alternatives is essential reading for students of criminology, criminal justice and law, as well as for other scholars and activists concerned about social justice, policing, courts, imprisonment, mass supervision, rights and privatized justice. The book’s emphasis upon the importance of imagination, experimentation, innovation and debate aims to promote an optimism that there are always alternatives to inequality, domination and oppression.-- Back cover
Includes bibliographical references and index.
Keywords: Criminal justice, Administration of